COMMUNICATION STRATEGIES OF GRADE 1 TEACHERS IN FACILITATING LEARNING TRANSITIONS FOR ELEMENTARY SCHOOL STUDENTS IN PURBAGANDA VILLAGE - Fany Saputri; Zuhriah Zuhriah (Program Pascasarjana UIN Sumatera Utara, 2026)
This study explores the communication strategies used by a first-grade teacher in facilitating students’ learning transition at an elementary school in Purbaganda Village. Employing a descriptive qualitative approach, the study collected data through classroom observation, in-depth interviews with the first-grade teacher as the main informant, supporting information from first-grade students, and documentation of learning activities. The findings show that the teacher applies adaptive communication strategies based on students’ emotional and academic readiness during the early transition period. These strategies include the use of simple and repetitive language, warm interpersonal interaction, play-based activities, and nonverbal communication such as facial expressions, voice intonation, and body movements. These practices help students gradually adjust to classroom routines, feel more comfortable in the new environment, and participate more confidently in learning. This study contributes by showing that, in the context of a rural elementary school, teacher communication functions not only as a medium for delivering instruction but also as an adaptive support mechanism in easing first-grade students’ transition into formal schooling